2010
DOI: 10.1186/1476-8518-8-2
|View full text |Cite
|
Sign up to set email alerts
|

CpG oligodeoxyribonucleotides protect mice from Burkholderia pseudomallei but not Francisella tularensis Schu S4 aerosols

Abstract: Studies have shown that CpG oligodeoxyribonucleotides (ODN) protect mice from various bacterial pathogens, including Burkholderia pseudomallei and Francisella tularensis live vaccine strain (LVS), when administered before parenteral challenge. Given the potential to develop CpG ODN as a pre-treatment for multiple bacterial biological warfare agents, we examined survival, histopathology, and cytokine data from CpG ODN-treated C57BL/6 mice to determine whether previously-reported protection extended to aerosoliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 13 publications
1
31
2
Order By: Relevance
“…Unlike the Y. pestis KIM D27 data reported here, however, CpG ODN treatment exacerbated disease in the Salmonella-infected mice, resulting in greater mortality (34). Conversely, treatment of mice with CpG ODN reduces lung bacterial burden and improves survival during lethal respiratory infections with K. pneumoniae and B. pseudomallei (25,31,32,59). Therefore, our KIM D27 plague model appears to be unique in that CpG ODN treatment increases the pulmonary bacterial burden while simultaneously promoting the survival of the host.…”
Section: Discussioncontrasting
confidence: 38%
“…Unlike the Y. pestis KIM D27 data reported here, however, CpG ODN treatment exacerbated disease in the Salmonella-infected mice, resulting in greater mortality (34). Conversely, treatment of mice with CpG ODN reduces lung bacterial burden and improves survival during lethal respiratory infections with K. pneumoniae and B. pseudomallei (25,31,32,59). Therefore, our KIM D27 plague model appears to be unique in that CpG ODN treatment increases the pulmonary bacterial burden while simultaneously promoting the survival of the host.…”
Section: Discussioncontrasting
confidence: 38%
“…infection (18). Other studies have shown that prior administration of known TLR agonists reduces overall organ burdens and increases survival following subsequent F. tularensis infection (46)(47)(48). However, other properties likely also contribute to the limited systemic replication of the ⌬0831 bacteria, since the Schu S4 ⌬0831 strain also failed to replicate in the spleens and livers of mice when administered systemically via i.p.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that such treatments are not universally successful. For example, recent studies have demonstrated that a preexposure CpG treatment strategy failed to protect mice that were subsequently infected with the highly virulent F. tularensis strain SchuS4 (46). Furthermore, there are no reported data on the efficacy of CpG treatment given postexposure against highly virulent pathogens.…”
Section: Proinflammatory Cytokinesmentioning
confidence: 95%